Diferentes sistemas de almacenamiento de granos en el Cantón Babahoyo - Baños García, Mauricio Daniel (2020)
The storage time and the preservation of its characteristics or quality are closely related to the tacit of humidity and the temperature of the grain mass. Each fruit must have an appropriate moisture content so that it can be stored safely and with the corresponding storage system. For this motion the importance of the elaboration of the present exploration, with which the different grain storage systems and their individual benefits will be disclosed, making the farmer know which is the most recommended for their production. The present work sought to carry out an analysis of the grain storage systems used in the Babahoyo Canton, managing to identify the most option for the storage of agricultural grain production and the one that provides the greatest benefits to farmers. During the course of the investigation of this practical study, a short tour was made of sectors where there are plantations that produce grains and a small dialogue was held with the farmers to obtain their point of view regarding the grain storage systems. This investigation is carried out in the traditional way and in which this stage lasted for several weeks, achieving a space for direct dialogue with the plantation owners and obtaining direct conclusions. It was found that most of the farmers who were the object of the present study use storage systems that are of the empirical type, silos or warehouses; maintaining its production to the collection of certain elements that cause prejudice to its production in which it was identified that the most option due to the greatest benefits it shows is the storage in Silos Chapas.